Morbidity in Newborns Readmitted Into a Hospital After Discharge From a Maternity Unit During the First 28 Days of Their Lives – Results From the Rhine-Main Area, Germany - Anagnostou, Anastasia; Schrod, Lothar; Jochim, Judith; Enenkel, Jürgen; Krill, Winfried; Schlößer, Rolf Lambert (Zeitschrift für Geburtshilfe und Neonatologie, 2020)
Background The neonatal period can be associated with a multitude of medical and social problems. Little is known about the reasons that lead to neonatal readmissions in a pediatric hospital and their individual outcomes.Objective To record the diagnosis of neonatal admissions in a pediatric hospital after discharge from a maternity unit. Predictive parameters are to be identified and a possible trend over the years is to be examined.Methods The medical history of newborns admitted to a pediatric hospital in the Rhine-Main area from 01/01/2004 to 31/12/2013 was retrospectively analyzed based on provided medical files.Results The data of 2851 newborns was recorded. 72% of the patients were delivered by vaginal birth. During the period under examination, there was a certain fluctuation although no significant trend in the number of admissions per year (p=0.062). The most frequent primary diagnoses were jaundice (27%), newborn infection (12.4%), and feeding problems (12.3%). Exclusively breastfed newborns had fewer feeding problems than newborns with a mixed or purely formula diets (p < 0.001).Conclusions The results of this study showed that the hospital readmissions of newborns throughout the years did not increase. Unfortunately, owing to the retrospective character of the study, it is not possible to make a clear statement as to whether hospitalization can be prevented with more intensive preventative measures. A prospective study on this matter is being planned.
Keywords: neonatology; neonates; perinatal; perinatal Mortality